Marseille & Western Provence : includes Aix-en-Provence, Arles, Avignon, Les Baux, Camargue - Tomasetti, Kathryn (Footprint focus., 2014)
Footprintfocus explores this popular French destination, which was European Capital of Culture 2013, and has been fully updated to incorporate the myriad of changes that have occurred in the city.